2020
DOI: 10.5194/acp-20-203-2020
|View full text |Cite
|
Sign up to set email alerts
|

Local and synoptic meteorological influences on daily variability in summertime surface ozone in eastern China

Abstract: Abstract. Ozone pollution in China is influenced by meteorological processes on multiple scales. Using regression analysis and weather classification, we statistically assess the impacts of local and synoptic meteorology on daily variability in surface ozone in eastern China in summer during 2013–2018. In this period, summertime surface ozone in eastern China (20–42∘ N, 110–130∘ E) is among the highest in the world, with regional means of 73.1 and 114.7 µg m−3, respectively, in daily mean and daily maximum 8 h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(90 citation statements)
references
References 94 publications
7
83
0
Order By: Relevance
“…Similar to our previous study for 2013-2017(Li et al, 2019a, the most important meteorological predictor variables in the MLR model are daily maximum temperature for the NCP and meridional wind at 850 hPa for the PRD. These dominant meteorological parameters are also consistent with the findings from other studies (Gong and Liao, 2019;Wang et al, 2019;Han et al, 2020). Hot weather is the main meteorological driver for the NCP, and we will elaborate on this in the next section.…”
Section: Figure 2 (Middle Panel)supporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our previous study for 2013-2017(Li et al, 2019a, the most important meteorological predictor variables in the MLR model are daily maximum temperature for the NCP and meridional wind at 850 hPa for the PRD. These dominant meteorological parameters are also consistent with the findings from other studies (Gong and Liao, 2019;Wang et al, 2019;Han et al, 2020). Hot weather is the main meteorological driver for the NCP, and we will elaborate on this in the next section.…”
Section: Figure 2 (Middle Panel)supporting
confidence: 90%
“…On the other hand, we find that meteorology mitigated ozone pollution increases over western China, northeastern China, and the Shandong Peninsula. Summer ozone in the Shandong Peninsula is strongly affected by maritime inflow (J. Zhang et al, 2019;Han et al, 2020) which increased over the 2013-2019 period ( Figure S1).…”
Section: Figure 2 (Middle Panel)mentioning
confidence: 99%
“…Poleward of the midlatitudes, the strength of r(T, O 3 ) decreases nearly monotonically over land, reaching either weak values or significantly negative correlations (Figure 3a). The O 3 -temperature relationship is varied equatorward of the midlatitudes; but, in the zonal mean, r(T, O 3 ) decreases to negative values south of 30 • N. Previous work by Rasmussen et al (2012) and Brown-Steiner et al (2015) in the United States and Han et al (2020) and Lu, Zhang, Chen, et al (2019) in China showed a similar latitudinal gradient of r(T, O 3 ). Despite the general tendency of a positive-to-negative relationship between O 3 and temperature with decreasing latitude, there are regions at low latitudes with significant positive correlations between O 3 and temperature (Central America, Sahel, the south coast of the Arabian Peninsula, Indo-Gangetic Plain; Figure 3a).…”
Section: O 3 -Meteorology Relationshipsmentioning
confidence: 74%
“…Furthermore, the RH presents a good correlation with the EOF1 time series (R = 0.59). Han et al (2020) also found that RH is the most important factor affecting O3 in the YRD. However, it is still unclear how the change in different weather systems causes the variation in RH, and how the RH variation impacts the other meteorological factors and O3 accumulation.…”
Section: Characteristics Of O3 Variability Based On the Eof Analysismentioning
confidence: 79%
“…3b, RH is the most crucial factor and its variation is similar to the variation in the total meteorological impact. Han et al (2020) also found that RH is the most influential factor in the central and south parts of eastern China. The East Asian summer monsoon plays a key role in affecting the local RH, and meanwhile it might bring a certain amount of O3 from the south area.…”
Section: Quantifying the Effects Of Meteorological Conditionsmentioning
confidence: 83%